2017
DOI: 10.1111/jdv.14712
|View full text |Cite
|
Sign up to set email alerts
|

Educational and practice gaps in the management of volar melanocytic lesions

Abstract: We found one major educational gap in the recognition of low-risk lesions with high rates of biopsy of the fibrillary pattern. Recognizing low-risk dermoscopic patterns could reduce the rate of biopsy of AMN by 23.3%. We identified two major practice gaps, poor patient compliance with follow-up and the potential insensitivity of the three-step algorithm to small multicomponent acral melanocytic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…However, the current literature on this topic is scarce. Data from Mayo clinic suggested that 6-mm acral melanomas could be missed when using the three-step algorithm 22 . Moreover, we reported two exceptional cases of evolving small ALMIS (4.5 mm and 5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current literature on this topic is scarce. Data from Mayo clinic suggested that 6-mm acral melanomas could be missed when using the three-step algorithm 22 . Moreover, we reported two exceptional cases of evolving small ALMIS (4.5 mm and 5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical three-step algorithm recommends a clinical cutoff for surgical excision when an acquired acral melanocytic lesion has a non-typical dermoscopic pattern, lesion diameter ≥7 mm and patient age >50 years, 87 The algorithm has sensitivity, specificity, PPV and NPV rates of 80%, 88%, 44% and 97%, respectively. 88 Notably, the low overall sensitivity may have been related to the relatively high frequency of small multicomponent AM diagnoses. Additionally, fibrillar pattern was commonly misclassified as a high-risk pattern by physicians.…”
Section: Key Pointsmentioning
confidence: 99%
“…Some dermoscopic algorithms and scores have been proposed to assist in both the differentiation of AM from benign lesions and early AM detection. The clinical three‐step algorithm recommends a clinical cutoff for surgical excision when an acquired acral melanocytic lesion has a non‐typical dermoscopic pattern, lesion diameter ≥7 mm and patient age >50 years, 87 The algorithm has sensitivity, specificity, PPV and NPV rates of 80%, 88%, 44% and 97%, respectively 88 . Notably, the low overall sensitivity may have been related to the relatively high frequency of small multicomponent AM diagnoses.…”
Section: Acral Melanomamentioning
confidence: 99%
“…Based on these characteristic dermoscopic findings, in 2007 our group proposed a dermoscopic 3-step algorithm for the management of acral melanocytic lesions [3] and then, revised it in 2011 [4]. Recently, several studies were reported which examined utility of the 3-step algorithm [5][6][7]. In these studies, the 3-step algorithm generally worked well, however, in one study, the algorithm missed one lesion of AM, 0.5 mm in Breslow thickness.…”
Section: Re-revisionmentioning
confidence: 99%
“…One possible problem in using the 3-step algorithm is judgment of whether the FP is regular or irregular. According to Costello et al, physicians often did not recognize the regular FP as a benign pattern [6]. The FP is characterized by densely packed brownish fibrillar lines arranged in a parallel fashion and crossing the skin markings.…”
Section: Re-revisionmentioning
confidence: 99%